Preparation and physical properties of gelatin/CMC/chitosan composite films as affected by drying temperature - Jahit, I.S.; Nazmi, N.N.M.; Prof. Ts. Dr. Mohd Ikmar Nizam Bin Mohamad Isa; Sarbon, N.M. (Universiti Putra Malaysia, 2024)
This study examined the effects of drying temperatures (25 and 45 °C) on the physical properties of different formulations of gelatin/CMC/chitosan composite films. The physical properties of each formulated film were assessed via Fourier Transform Infra-Red (FTIR) spectroscopy, X-Ray Diffractometry (XRD), Water Vapour Permeability (WVP) and biodegradability. The incorporation of CMC and chitosan significantly influenced film properties. Increased chitosan concentrations reduced the film’s amorphous character by increasing its crystalline structure. The blended films also exhibited amino peaks that shifted from 1542 to ~1548 cm-1 while NH and/or OH peaks shifted from 3384 to 3288 cm-1. Formulation E had the second lowest WVP for both drying condition and the highest weight loss for biodegradability after burial in soil for 5 days. In conclusion, different temperature did not affect the properties of film produced and formulation E qualified as ‘high quality packaging material’ with promising potential for the food packaging industry.